Data-Driven prioritisation of antibody-drug conjugate targets in head and neck squamous cell carcinoma. (May 2018) - Hanemaaijer, Saskia H.; van Gijn, Stephanie E.; Oosting, Sjoukje F.; Plaat, Boudewijn E.C.; Moek, Kirsten L.; Schuuring, Ed M.; van der Laan, Bernard F.A.M.; Roodenburg, Jan L.N.; van Vugt, Marcel A.T.M.; van der Vegt, Bert; Fehrmann, Rudolf S.N.
Highlights: Antibody-drug conjugates (ADCs) are an emerging class of cancer therapeutics, targeting tumor-specific antigens. Functional genomic mRNA profiling was utilized to perform a data-drive prioritisation of 55 different ADC targets in HNSCC. GPNMB was identified as top candidate ADC target. GPNMB expression was found in 92% of 414 HNSCC samples. Abstract: Background: For patients with recurrent or metastatic head and neck squamous cell carcinoma (HNSCC) palliative treatment options that improve overall survival are limited. The prognosis in this group remains poor and there is an unmet need for new therapeutic options. An emerging class of therapeutics, targeting tumor-specific antigens, are antibodies bound to a cytotoxic agent, known as antibody-drug conjugates (ADCs). The aim of this study was to prioritize ADC targets in HNSCC. Methods: With a systematic search, we identified 55 different ADC targets currently targeted by registered ADCs and ADCs under clinical evaluation. For these 55 ADC targets, protein overexpression was predicted in a dataset containing 344 HNSCC mRNA expression profiles by using a method called functional genomic mRNA profiling. The ADC target with the highest predicted overexpression was validated by performing immunohistochemistry (IHC) on an independent tissue microarray containing 414 HNSCC tumors. Results: The predicted top 5 overexpressed ADC targets in HNSCC were: glycoprotein nmb (GPNMB), SLIT and NTRK-like family member 6, epidermal growth factor receptor, CD74 and CD44. IHC validation showed combined cytoplasmic and membranous GPNMB protein expression in 92.0% of the cases. Strong expression was seen in 65.9% of the cases. In addition, 86.5% and 67.7% of cases showed ≥5% and >25% GPNMB positive tumor cells, respectively. Conclusions: This study provides a data-driven prioritization of ADCs targets that will facilitate clinicians and drug developers in deciding which ADC should be taken for further clinical evaluation in HNSCC. This might help to improve disease outcome of HNSCC patients.